Analisis Fungsi Perencanaan, Pengambilan Keputusan, Dan Hubungan Bisnis Dalam Manajemen Pada Novel Catatan Akhir Kuliah 2.0 Karya Sam@Maulasam - Syawalica Fifah Nurcahya; Windi Wulandari; Eva Dwi Kurniawan (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to determine the functions of management in the novel end of lecture notes 2.0 by Sam@maulasam. This novel, published in 2017. The data collection techniques used are reading techniques and analysis techniques. The method used in this research is a qualitative method with descriptive analysis. The data source in this research is the literary work Novel End of Lecture Notes 2.0 by Sam@maulasam. Based on the research results, it can be concluded that the functions of planning, decision making and business relationships influence the running of a business.